High Speed rail transport valuation and conjuncture shocks - Couto, Gualter (2019)
In the present paper we derive the optimal investment policy of investment in the high speed rail (HSR) project, under uncertainty, using the real options analysis (ROA) framework. We assume that the HSR demand, the main source of uncertainty, follows a geometric brownian motion with random jumps, complying with abrupt change of level caused by random events. The occurrence of such events is caused by external shocks. We assess the impact of these shocks in the HSR demand threshold, along with the investment opportunity value, and the option to differ. We consider several distributions for these jumps, and we compare with the base-line case (where exogeneous jumps are not considered).